Neospora caninum infection in dairy cattle in Egypt: a serosurvey and associated risk factors - Abdelfattah Selim; Ayed Alshammari; Hattan S. Gattan; Mohamed Marzok; Mohamed Salem; Omar A. AL-Jabr (Scientific Reports, 2023)
Abstract Neospora caninum (N. caninum) is one of the causative agents that causing cattle abortion, and severe economic losses. Due to the scarcity of data on N. caninum infection in Egyptian cattle, the purpose of this study was to estimate the seroprevalence and determine the risk factors for parasite infection. In four governorates in northern Egypt, 540 blood samples from cattle were taken, and tested using a commercial ELISA kit. The overall seroprevalence of N. caninum in examined cattle was 28.89%. A multivariate logistic regression model determined that age (OR = 2.63, P < 0.001), manual milking (OR = 1.39, P = 0.14), abortion history (OR = 2.78, P < 0.0001), repetition of estrus (OR = 2.31, P < 0.0001), and contact with dogs (OR = 2.57, P < 0.0001) were significant risk factors. The findings proved that N. caninum infection was one of the factors contributing to abortion and financial losses in dairy cattle in Egypt. Therefore, the application of sanitary security and control programs is very important in dairy farms.